“Undisturbed and lovely” : Dietrich Bonhoeffer and the theological education of the Confessing Church during the Zingsthof Period - Schulze, Alexander (Stellenbosch Theological Journal, 2023)
While Bonhoeffer’s illegal theological training is inseparably and quite correctly located with the name Finkenwalde, the first weeks of the seminary at the Zingsthof deserve consideration. This article emphasizes the foundational and formative function of the improvised but notably successful beginning at the Baltic Sea and supports the assumption that Bonhoeffer knew what he was doing from the very start. Characteristics such as the contemplative time in the morning, the half-hour singing before noon, and the open discussions in the evenings originated there, as did the highly efficient communication methods of the seminary. Commenced lectures as well as accompanying practical exercises were continued in Finkenwalde with almost no delay. The Zingsthof had not been closed but was intended as an interim. Therefore, it was secondary where what had been established there was to be continued. Significantly, after Finkenwalde was sealed off by the state police, Bonhoeffer once again invited all seminarians to a final gathering at the Zingsthof in the late summer of 1938.